Substance Use Disorders and Psychoactive Drug Poisoning in Medically Authorized Cannabis Patients: Longitudinal Cohort Study. (July 2022) - Zongo, Arsène; Lee, Cerina; El-Mourad, Jihane; Dyck, Jason R. B.; Hyshka, Elaine; Hanlon, John G.; Eurich, Dean T.
Objectives: Poisoning from psychoactive drugs and substance use disorders (SUD) have been reported among non-medical cannabis users. However, little is known about medical cannabis users and their risk for poisoning and/or development of SUD. This study assessed the risk of emergency department (ED) visits or hospitalization for 1) poisoning by psychoactive drugs and 2) mental/behavioural disorders due to the use of psychoactive drugs and other substances, in medically authorized cannabis patients in Ontario, Canada from 2014–2017. Methods: A cohort study of adult patients authorized for medical cannabis that were matched to population-based controls. ED visit/hospitalization were assessed with a main diagnostic code for: 1) poisoning by psychoactive drugs; 2) mental and behavioural disorder due to psychoactive drugs or other substance use. Conditional Cox proportional hazards regressions were conducted. Results: 18, 653 cannabis patients were matched to 51, 243 controls. During a median follow-up of 243 days, the incidence rate for poisoning was 4.71 per 1, 000 person-years (95%CI: 3.71–5.99) for cases and 1.73 per 1, 000 person-years (95% CI: 1.36–2.19) for controls. The adjusted hazard ratio (aHR) was 2.45 (95%CI: 1.56–3.84). For mental/behavioural disorders, the incident rates were 8.89 (95% CI: 7.47–10.57) and 5.01 (95% CI: 4.36–5.76) in the cannabis and the controls group. The aHR was 2.27 (95%CI: 1.66–3.11). No difference was observed between males and females ( P -value for interaction > 0.05). Conclusions: Our study observed a short-term increased risk of ED visit/hospitalization for poisoning or for mental/behavioural disorders (from use of psychoactive drugs and other substances)- in medically authorized cannabis patients.